An Empirical Study and simulation analysis of MAC layer model using AWGN channel of WiMAX technology - Mukesh Patidar; Ankit Jain (AG Volumes, 2021)
The IEEE 802.16 specification defines WiMAX, a wireless broadband data transmission technology. It enables high-speed data transmission over a wide range and remains inexpensive. This is a point-tomulti point wireless network technology that can also be used in other network applications such as wireless sensor networks. In this article, we will use MATLAB Simulink to analyze the MAC tier model on WiMAX. This MAC tier model can be used to evaluate WiMAX performance in multiple scenarios such as high data rates, modulation schemes, and channel conditions. The proposed simulation model has reduced simulation time and performance. In this analysis, various modulation techniques such as QPSK and QAM were used on the AWGN channel and the simulation results were compared by SNR and BER.